A qualitative study of the relationship between interorganizational internet communication and purchasing performance. (11th November 2008) - Cai, Shaohan; Jun, Minjoon
We develop a conceptual framework that integrates three key dimensions of interorganizational internet communication, such as formality, frequency and diversity, their two antecedents, perceived internet security risks and norms of internet information sharing and one consequence, purchasing performance. The linkages between these constructs were empirically tested through a series of interviews with purchasing managers. The results reveal that the frequency and diversity of internet communication play an important role in enhancing purchasing performance; formality exerts a minimal impact on the performance and perceived internet security risks significantly affect norms of internet information sharing, and in turn frequency and diversity.